Does corporate governance affect bank risk management? Case study of Indonesian banks. Issue 2 (23rd October 2020) - Permatasari, Ika
Abstract : Purpose: The purpose of this study is to examine the relationship between corporate governance and risk management of Indonesian banks. Design/methodology/approach: Implementation of good corporate governance is measured by good corporate governance composite rating, which is the result of bank's self-assessment. Bank risk managements are measured by market risk, credit risk, liquidity risk and operational risk. Findings: The study results showed that good corporate governance implementation in Indonesia was able to influence bank risk. There were differences in credit risk, liquidity risk and operational risk in banks with different governance ratings, but not at market risk. Originality/value: The effectiveness of risk management and good corporate governance implementation is needed to enable banks to identify problems early, to follow up on rapid improvements and to be more resilient to crises. This study is an analysis of the relationship between corporate governance and banks' risk management in Indonesia. In particular, risk management is measured by four risks: market risk, credit risk, liquidity risk and operation risk.